Assessing the Agency in Media Narratives for Community-based Peacebuilding - Onguny, Philip; Gillies, Taylor (Global Media Journal - German Edition, 2020)
This article assesses the dominant debates about the agency in media narratives for community-based peacebuilding. By locating the common challenges facing the agency in media narratives for the purposes of community-based peacebuilding, the article contributes to the ongoing debates on ways in which media discourses can be tailored toward the prevention, management, and resolution of conflicts between, within and among communities. This is predicated on the assumption that conflict is a function of discourse, and that media narratives take active part in the construction, negotiation, and circulation of discourse, all of which inform the degree of congruity between news content and expected outcomes. The primary objective of this article is therefore to generate conceptual and theoretical debates on the agentic and formative roles media narratives play in community-based peacebuilding.